SYNTHESIS AND COORDINATION CHEMISTRY OF ITACONIC ESTERTIN(IV) COMPLEXES - JUNG, OS; JEONG, JH; SOHN, YS (ELSEVIER SCIENCE SA LAUSANNE, 1992)
New itaconic estertin(IV) complexes CH3OOCCH2CH(COOCH3)CH2Sn(L)Cl2 (1, L = S2CNMe2; 2, L = (Pz)3BH; 3, L = OH) were synthesized and characterized by means of X-ray crystallography and spectroscopy. The crystal structures of 1 (P2(1)/n; a = 7.830(1), b = 13.262(1), c = 16.958(2) angstrom, beta = 91.269(9)-degrees; Z = 4; R = 0.043) and 3 (P2(1)/n; a = 11.611(2), b = 12.301(2), c = 12.435(2) angstrom, beta = 101.02(1)-degrees; Z = 4; R = 0.043) show that each tin atom approximates to octahedral geometry via an intramolecular carbonyl-to-tin coordination in addition to either chelation of the dithiocarbamate (for 1) or hydroxo-bridging (for 3). The reaction of 1 or 3 with sodium sulfide giveS CH3OOCCH2CH(COOCH3)CH2 Sn(L)S (4, L = S2CNMe2; 5, L = OH), whereas the same reaction of 2 does not give the analogous chemical product but instead allows dissociation of the trispyrazolylborate ligand.
Keywords: SUBSTITUTED ALKYLTIN HALIDES; SN-119 CHEMICAL-SHIFTS; CRYSTAL-STRUCTURE; SPECTROSCOPIC ASPECTS; LEWIS ACIDITY; TIN; DIMETHYLDITHIOCARBAMATE; CL3SNCH2CH2CO2R; DERIVATIVES; TRIHALIDES